Use of N-Acetyl-L-Cysteine Antioxidant in Cryopreservation of Cord Blood Nucleated Cells - Makashova, Ekaterina Ye.; Zubova, Oksana L.; Zubov, Pavel M. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):183.